DAMPAK REFORMASI EKONOMI DAN POLITIK KUBA TERHADAP HUBUNGAN BILATERAL DENGAN AMERIKA SERIKAT TAHUN 2008-2016 - Andry Atthariqa; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describes the impacts of Cuba political economic reform bilateral relations with the United States. Cuba is a communist country since Fidel Castro. United States cut the diplomatic relations with Cuba since 1961 and United States imposing the economic embargo to Cuba. Over the last five decades bilateral relations between the United States and Cuba was worse.This research theoretically has built with Liberalism perspectives on International Relations and supported by Kantian Peace Triangle theories. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data which is gotten and collected through the books, journal, thesis and from internet or websites that related to the research.This research shows that the Cuban political economic reforms in the reign of Raul Castro has an impact on bilateral relations between the United States and Cuba. This bilateral relations softened since Raul Castro led Cuba's political and economic reform. United States began to reopen embassies in Havana, Cuba. In addition, the President of the United States also made a visit to Cuba with an agenda to discuss the termination of Cuban economic embargo by the United States of America.Keyword: Reform, Embargo, Bilateral Relations, Economics